2009
DOI: 10.1039/b815338h
|View full text |Cite
|
Sign up to set email alerts
|

Redox switching and oxygen evolution electrocatalysis in polymeric iron oxyhydroxide films

Abstract: Outstanding issues regarding the redox switching characteristics and the oxygen evolution reaction (OER) electrocatalytic behaviour of multicycled iron oxyhydroxide films in aqueous alkaline solution have been examined. Charge percolation through the hydrous layer has been quantified, using cyclic voltammetry, in terms of a charge transport diffusion coefficient D CT which admits a value of ca. 3 Â 10 À10 cm 2 s À1 . Steady-state Tafel plot analysis and electrochemical impedance spectroscopy have been used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
102
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 49 publications
12
102
1
Order By: Relevance
“…In such cases, the experimentally observed kinetic parameters represent a combination of the parameters expected for the competing pathways, the exact value of which depends on the fraction of catalytic sites following each individual pathway. Then again, Lyons and Brandon 92 have shown that the fractional reaction order m OH À = 1.5 observed for an 'aged' passive oxide coated iron electrode can be rationalised by admitting Temkin rather than Langmuir adsorption conditions. (b) Open circuit potential decay.…”
Section: View Article Onlinementioning
confidence: 98%
See 3 more Smart Citations
“…In such cases, the experimentally observed kinetic parameters represent a combination of the parameters expected for the competing pathways, the exact value of which depends on the fraction of catalytic sites following each individual pathway. Then again, Lyons and Brandon 92 have shown that the fractional reaction order m OH À = 1.5 observed for an 'aged' passive oxide coated iron electrode can be rationalised by admitting Temkin rather than Langmuir adsorption conditions. (b) Open circuit potential decay.…”
Section: View Article Onlinementioning
confidence: 98%
“…Lyons and coworkers 17,92 have applied the Aoki model to the voltammetric data obtained for hydrous Fe oxide coated electrodes. In particular, they note that the i p /v 1/2 proportionality can be readily obtained at reasonable values of sweep rate for thick layers whereas the i p /v proportionality, suggesting the operation of Nernstian equilibrium throughout the dispersed layer during redox switching, is observed over an extended range of sweep rates for thin layers.…”
Section: Charge Transport In Transition Metal Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been noted that dispersed hydrated oxide materials exhibit good electrocatalytic potentiality due to their skeletal nature as the latter structural feature permits a major increase in the number of oxyions participating in the electrode reaction. 11,30 Indeed, with microdispersed species the boundary between the solid and aqueous phase may be nebulous as the two phases virtually intermingle. This will be an important consideration when a model for the OER is developed.…”
Section: Preparation and Voltammetry Of Hydrous Iron Oxidesmentioning
confidence: 99%